The Future of International Arbitration in Australia - Monichino Albert (Victoria University Law and Justice Journal, 2015)
The International Arbitration Act 1974 (Cth) is a Commonwealth Act that implements Australia’s obligations to enforce and recognise foreign arbitration agreements and arbitral awards under the Convention on the Recognition and Enforcement of Foreign Arbitral Awards 1959. The avowed purpose of the reforms was to position Australia as an attractive seat for arbitration in the Asia-Pacific region. Given the elapse of time since the amendments, it is opportune to reflect on how far Australia has come in that time, and the challenges and opportunities going forward. Undoubtedly, there has been a shift in the attitude of Australian courts towards greater judicial support and less judicial intervention in the arbitration process. Based on an extensive discussion of a particular dispute, TCL v Castel, the paper highlights that the High Court’s judgment confirms Australia is an arbitration-friendly jurisdiction. Had the decision gone the other way, it may have sounded the death knell for international arbitration in Australia.